RESEARCH ON THE EFFECTIVENESS OF TRAINING TECHNOLOGIES’ IMPLEMENTATION IN STUDENT THEATER - Popovych, Ihor; Lymarenko, Lidiia; Tereshenko, Natalia; Kornisheva, Tetiana; Yevdokimova, Olena; Koverznieva, Anna; Aleksieieva, Mariia (Revista Inclusiones, 2021)
The purpose of the research is to determine the effectiveness of implementation and the feasibility of using training technologies in student theater. Research methodology consisted of aesthetic, artistic and theatrical, psychological and pedagogical ideas, theories about the role of art of student theater. The expediency of training technologies’ implementation of teaching as an effective practical tool of theatrical pedagogy in order to develop the stage-pedagogical action and to increase the artistic-pedagogical level of future teachers has been proved. The author’s system of use and interaction of training technologies of teaching in the student theater is presented. It is stated that the successful educational process of student theater is ensured by the active use of theatrical-training technologies that develop the student’s personality, his stage-pedagogical action. It is established that the implementation of training technologies in the activities of the student theater significantly complements the traditional educational and professional training of specialists and affects the psychological content parameters of their motivational sphere (p≤.05; p≤.01). It is substantiated that the use of training technologies allows to develop the psychophysical apparatus of the teacher, his communicative, kinesthetic and spatial-organizational actions and to increase the level of artistic and pedagogical activity.